Game on : uma experiência com games na formação de professores de língua inglesa - Avelar, Michely Gomes (2019)
The purpose of this project is to encourage reflection on games in English language teaching through the bias of multiliteracies. To this end, we discuss the perception of English language teachers (in education and professional levels) regarding the language practices that emerge from games. Using games to reflect on language practices is based on the multiplicity of language and culture provided by digital games. The perspectives and proposals presented are based on studies on multiliteracies (COPE; KALANTIS, 2009; ROJO, 2012; GEE, 2003), reflecting on new modalities of language emerged by contemporary society, and articulate the use of digital technologies to language education (GEE, 2003, 2004; LYNN, 2013; PRENSKY, 2001, 2012; SOUZA, 2011; MONTE MÓR, 2010, 2018). The research considered a qualitative approach based on the experiences of the researched and researched subjects (LARROSA, 2002, 2018) and the studies of complexity (MORIN, 2015). I also add that different practices of reading and interaction in English can be triggered from games, stimulating social and intercultural development. The choice for the digital game is justified by the fact that it is part of the daily life of children and adolescents and considering that articulating the use of digital technologies and the students' experiences - as players - to the educational context is an opportunity to combine multi-skills and games, making language teaching (GEE, 2003; PRENSKY, 2006). Information gathering is carried out through an extension action with English language teachers in initial and continuing education to provide experience with digital games as a multi-tool practice. It is considered as research instruments: questionnaires, reports, my notes and the interactions of participants in the Whatsapp group. This study aims to point out the possibilities of dialogue between the multiliteracies and English Language teachers in Education, encouraging them reflect on critical use of games as language practices.